Microcephaly in Infants, Pernambuco State, Brazil, 2015 (Emerg Infect Dis, 2016)
We studied the clinical characteristics for 104 infants born with microcephaly in the delivery hospitals of Pernambuco State, Brazil, during 2015. Testing is ongoing to exclude known infectious causes. However, microcephaly peaked in October and demonstrated central nervous system abnormalities with brain dysgenesis and intracranial calcifications consistent with an intrauterine infection.